Dyskeratosis congenita presenting with dysphagia - Kalpana Gupta (Indian Dermatology Online Journal, 2016)
Dyskeratosiscongenita (DKC) is a genetically heterogeneous disease of defective telomere maintenance that may demonstrate different patterns of inheritance. It is characterized by thetriad of dystrophy of the nails, leukokeratosis of the oral mucosa, and extensive net-like pigmentation of the skin. We report a case ofDKC who presented with a chief complaint of dysphagia.